Trabajo, género y vida cotidiana en Iberoamérica - Viego, Valentina; de Camilo, Juliana A. O. (Ariadna Ediciones, 2023)
At the end of 2017, the Research Network on Work, Gender and Daily Life was created, with the support of the Ibero-American Postgraduate University Association (AUIP). 44 researchers from 19 universities in 11 Latin American countries participated in its initial constitution. After almost 6 years, this network has doubled in size: close to a hundred participants, in 36 universities and 13 countries in the region. This journey has allowed consolidated and training researchers to be convened at the end of 2022 to publish recent findings on the dynamics of gender inequalities in the productive and reproductive sphere. The result is condensed in this volume, which also constitutes an invitation for future collaborations and dialogues between the world of scientific knowledge and the social reality of women and dissidents in Ibero-America.